Trams: Bridging the Past and Future—Example Guidelines for Tram Redesign Illustrated by a Case Study from Korea - Fabio Dacarro; Guido Musante (Applied Sciences)
This study was inspired by an emerging trend in contemporary cities: the transformation of trams into mobile spaces for recreation, education, and work. Despite the growing popularity of this concept, which is linked to the search for more sustainable transport options, there is a marked lack of guidelines, methodological frameworks, and reference case studies necessary to support these projects. This study fills this gap by illustrating the design guidelines developed for a project in Gwangmyeong, a new Korean town. These guidelines provide a structured framework for converting existing trams into mobile venues such as restaurants, classrooms, and work and conference spaces. Employing the design thinking approach, the guidelines comprise three primary design phases—Understand, Define, and Materialize—each consisting of two sub-phases, and specify the technical tools, roles, and outputs needed. The proposed guidelines are illustrated using material from the Gwangmyeong project. As the first of their kind, these guidelines provide a valuable case study and reference materials for designers, offering possible benchmarks for the technical and financial evaluation of such projects. This study hopes to stimulate discussions on the development and refinement of similar methodologies, addressing the growing interest in design discourse.